Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5455/medarh.2020.74.270-274
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glasgow-Blatchford Score and Rockall Score in Patients with Upper Gastrointestinal Bleeding

Abstract: Introduction: Upper gastrointestinal bleeding can be a life-threatening condition and requires careful evaluation from the very first episode in order to reduce the risk of rebleeding, hemorrhagic shock and death. The outcome of a patient with upper gastrointestinal bleeding depends on resuscitation measures taken during admission to the hospital and an adequate assessment of the patient’s risk level. Aim: The aim of the study is to compare Glasgow Blatchford score and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…RS predicts mortality using pre endoscopic and endoscopic finding, while GBS predicts need for blood transfusion using basic clinical and laboratory data. A high score is associated with high risk of rebleeding, needing an intervention and vice versa [20].…”
Section: Discussionmentioning
confidence: 99%
“…RS predicts mortality using pre endoscopic and endoscopic finding, while GBS predicts need for blood transfusion using basic clinical and laboratory data. A high score is associated with high risk of rebleeding, needing an intervention and vice versa [20].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published in 2016 which included 16 studies found that GBS score was more accurate for both intervention and 30-day mortality than Rockall score and AIM65 [ 30 ]; another study found that the accuracy of GBS for predicting mortality was poor [ 31 ], and in a study of NVUGIB, pre-endoscopic and full RS were superior to GBS in predicting in-hospital mortality (AUC 0.842 for pre-RS, 0.804 for full-RS and 0.622 for GBS) [ 25 ]. In a study of 237 patients with both variceal and non-variceal UGIB, RS was superior to GBS [ 26 ]. A study which analyzed in-hospital mortality found that AIM65 was better than both GBS and full Rockall score in predicting mortality (AUC 0.955), regardless of variceal or non-variceal bleeding [ 24 ], while another study found that the accuracy of AIM65 was better than that of GBS for predicting 30-day mortality (AUC 0.706 versus 0.542) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the patients with no endoscopy performed represent a heterogenous group, with few studies regarding both mortality and the role of risk (non-endoscopic) scores in the prognostic evaluation. The mortality risk in the subgroup of patients without endoscopy is poorly evaluated in the literature; most studies included only patients with UGIB with endoscopy performed, and the absence of endoscopy represents one of the exclusion criteria in studies evaluating the performance of risk scores [ 1 , 3 , 4 , 10 , 24 , 25 , 26 , 27 ]. In this setting, a study evaluating the accuracy of prognostic scores for mortality in a subgroup of patients without endoscopy and with no known etiology for bleeding can be useful in order to predict the risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…The Rockall score, which includes both pre-and post-endoscopic components, has a high predictive capability for mortality [ 17 ]. However, because it requires several components, the Rockall score may be challenging to use in the ED [ 18 ]. The AIMS65 score was also identified as a good predictive factor for long-term hospitalization and in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%